HLA-Haploidentical Family Donors: The New Promise for Childhood Acute Lymphoblastic Leukaemia? - Ab Rahman, Syaza; Matic, Toni; Yordanova, Maya; Ariffin, Hany (Frontiers in Pediatrics, 2022)
Allogeneic haematopoietic stem cell transplantation (HSCT) is indicated in children with high-risk, relapsed or refractory acute lymphoblastic leukaemia (ALL). HLA-matched grafts from cord blood and stem cell repositories have allowed patients without suitable sibling donors to undergo HSCT. However, challenges in procuring matched unrelated donor (MUD) grafts due to high cost, ethnic disparity and time constraints have led to the exponential rise in the use of stem cells from human leukocyte antigen (HLA)-haploidentical family donors. Whilst HLA-haploidentical HSCT (hHSCT) performed in adult patients with acute leukaemia has produced outcomes similar to MUD transplants, experience in children is limited. Over the last 5 years, more data have emerged on hHSCT in the childhood ALL setting, allowing comparisons with matched donor transplants. The feasibility of hHSCT using adult family donors in childhood ALL may also address the ethical issues related to selection of minor siblings in matched sibling donor transplants. Here, we review hHSCT in paediatric recipients with ALL and highlight the emergence of hHSCT as a promising therapeutic option for patients lacking a suitable matched donor. Recent issues related to conditioning regimens, donor selection and graft-vs.-host disease prophylaxis are discussed. We also identify areas for future research to address transplant-related complications and improve post-transplant disease-free survival.